Utilização de substâncias naturais no controle de pulgões em cultivo orgânico de brócolis, Brassica oleracea var. itálica (Brassicaceae) - Santos, Adriano Jorge Nunes dos (2011)
The aim of this study was to evaluate the effect of aqueous extracts of leaves of neem (Azadirachta indica A. Juss), Meliaceae, leaves and foliage of bitter melon, in Brazil named melão-de-são-caetano (Mormodica charantia L.), Cucurbitaceae, Chili Pepper fruits (Capsicum frutescens), Solanaceae, black pepper seeds (Piper nigrum), Piperaceae, NeenMax® (neem oil) and water (control) to control aphid infestations in organic cultivation of Brassica oleracea var. italic, in Arapiraca city, Alagoas. Applications of the extracts to 10% (v/v) and formulated neem to 2% (v/v) containing 0.12% of the active ingredient azadirachtin, were performed weekly, during five weeks. The products were evaluated by the number of infested plants, percentage of leaves infested and, by the initial occurrence of infestation in each application period. The experiment was a randomized in blocks with four repetition. Each repetition was represented by a plot with 24 plants (3.0 m x 3.6 m) in single rows of beds of 0.50 meters in width, 0.90 m distant. There were no significant differences between treatments on F test (p <0.05) for both the variable of infested plants, and for percentage of infested leaves when the extracts were applied at 22 and 29 days after planting (DAP). In relation the initial occurrence of infestation, significant difference by F test at 5% probability at 50 DAP, with the NeenMax ® treatment, showing better performance (12.5%) in the field to control L. erysimi infestation in organic cultivation of broccoli.